[AR] Su’ubat Fahm Madmun al-Maddah wa al-Tawasul al-Lughawi fi al-Lughah al-Injiliziyyah al-lati Yuwajihuha al-Talabah al-Natiqun bi al-Lughah al-’Arabiyyah fi Markaz al-Lughat bi al-Jami’ah al-Islamiyyah al-‘Alamiyyah bi Maliziya: Difficulties in Understanding the Content of the Material and Linguistic Communication in English Faced by Arabic-Speaking Students at the Centre of Language and Pre-University Development IIUM (Afaq Lughawiyyah, 2024)
Centre for Language and Pre-University Academic Development (CELPAD) at the International Islamic University Malaysia aims to enhance English language skills among Arabic-speaking students through intensive courses designed to improve listening, speaking, reading, and writing abilities. Despite the comprehensive programs offered, students face significant challenges in both understanding academic content and effective linguistic communication. This study investigates the difficulties encountered by Arabic-speaking students at CELPAD, focusing on two main areas: comprehension of English course material and language communication skills. A quantitative research methodology was employed, using questionnaires distributed to a sample of 32 students from CELPAD. The data were analysed using SPSS to identify the major obstacles faced by students. The findings reveal that the most significant challenges in understanding course content include difficulties with comprehension strategies, interpreting test questions, and vocabulary limitations. Conversely, the primary obstacles in communication involve issues with speech fluency, grammar application, and pronunciation of complex terms. The study also found that less significant challenges pertain to the use of translation tools, the availability of reference materials, and the effectiveness of private tutoring. The study concludes that while some obstacles are inherent to the nature of learning a second language, others can be addressed through improved instructional strategies and better resource utilization. The results suggest that enhancing comprehension strategies and communication training could significantly benefit students' academic and linguistic development. The reliability of the research instruments was confirmed with Cronbach’s Alpha values of 0.861 for comprehension difficulties and 0.872 for communication challenges, indicating robust and reliable measures for the study's objectives.